Atlas microestrutural para otimização de procedimentos de soldagem - Amaral, Thiago de Souza (2016)
More complex and bigger structures have increased the applicability of low alloy high strength steels due to weight and cost reductions in these projects. One of the requirements for the use of these materials is the preservation of performance after welding. Meanwhile, the norms on which the Welding Procedures Specifications (WPS) are based have not yet considered the development of modern steel and its new production process, resulting in unnecessary welding costs that diminish the profits of the application of this type of steel. This thesis aimed to develop and evaluate an experimental methodology to guide the creation and control of welding procedures for structural steel through a microstructural atlas of the heat affected zone (HAZ) in a thermomechanical control process (TMCP), 65 ksi steel (ASTM A572 Grade 65). This steel was used in the project of an industrial building for CBMM in Araxá, Minas Gerais, Brazil. It is proposed that through a microstructural atlas of a given steel, it is possible to determine the range of cooling rates that the steel may suffer during welding without affecting mechanical properties and without risking cold cracks. When comparing the microstructure of steel welds performed in field conditions, it is possible to determine the heat input range for a given process in the preparation of a WPS. The selected case study is from a high strength low alloy class 65 ksi steel (ASTM A572 Grade 65) that was used in the structure of an industrial building. The steel was produced using TMCP. The atlas was created via the construction of a continuous cooling transformation diagram using physical simulation (dilatometer and Gleeble) of the coarse grain HAZ (GCHAZ). The characterization of the simulated region was performed by metallography and mechanical tests. The microstructure of real welds made by a qualified WPS were compared to the atlas in order to certify the correct use of parameters and to validate the method. The methodology was also qualified and the potential economic benefits were quantified (based only on the reduction of consumables used and the increased availability of the welding process machine) for the selected industrial project. The mapped microstructures varied from martensite (at high cooling rates) to pearlite/ferrite with large grain size (at low cooling rates). There was remarkable prevalence of bainitic microstructure in a wide range of cooling rates, consistent with the chemical composition of the steel studied. Comparisons with real weld microstructures showed the atlas is compatible with them, and that it can more accurately describe the effective thermal cycle xi that occurs in the coarse grain region of the HAZ (other regions were not included). The application of this methodology in the development of new WPS would allow greater flexibility in the welding procedures, including welding without preheating. In this respect alone, it was possible to forecast savings of approximately R$200,000.00, 1,000 hours of processing and 172 tonnes of carbon equivalent emissions.